A STUDY OF BIOFILM FORMATION IN INDWELLING CATHETER DEVICES IN ICU & PICU OF SRM MEDICAL COLLEGE HOSPITAL AND RESEARCH CENTRE: Life Sciences-Microbiology - MAHARAJA PANDIAN; SEKAR PASUPATHY (International Journal of Life Science and Pharma Research, 2022)
Biofilm is defined as an association of organisms in which microbial cells attached to each other on a living or non-living surfaces. Biofilm can be a threat to human health by the growth of organisms on medical implants such as prosthesis, heart valves and urinary catheter leading to infections. Moreover biofilm shows an increased resistance to antimicrobial agents. The objective of the study is to isolate and identify the biofilm producing organisms and their antibiotic sensitivity pattern in patients with indwelling various catheter. This study was carried out from Jun 2009 to 2011 Dec at the Department of Pediatrics & Microbiology, SRM MCH & RC, Chennai. About 120 indwelling catheter tips were received from various clinically diagnosed patients by Brain heart infusion broth (BHI) and incubated for 24hrs at 370C. After 24hrs incubation, one loop-full of sample was taken from BHI broth and inoculated in Cysteine Lactose Electrolyte Deficient agar(CLED).The detection of biofilm using crystal violet stain tube method was performed and it was confirmed by colorimetric analysis according to the optical Density(OD)value. Maximum biofilm producers were formed in 75 catheters out of 120 specimens. E.coli was the predominant organisms producing biofilm in indwelling catheter among the 75 isolates .The present study also proved that Staphylococcus aureus, Klebsiella sp. Enterococcus sp, Proteus mirabilis, Coagulase Nagative Staphyloccus (CONS) and Pseudomonas aeruginosa produced biofilm formation on indwelling catheter. Antibiotic Sensitivity pattern showed the E.coli and P.aeruginosa were resistant to all antibiotic compared with other isolates. E.coli and P.aeruginosa also frequently isolated from various cases of indwelling catheter patients but both organisms cause major problem in hospital acquired infection and resistant to all antibiotics.